Association between personality and tau-PET binding in cognitively normal older adults - Schultz, Stephanie A. (Brain Imaging Behav, 2020)
Personality traits such as Neuroticism and Conscientiousness are associated with Alzheimer disease (AD) pathophysiology in cognitively normal (CN) and impaired individuals, and may represent potential risk or resilience factors, respectively. This study examined the cross-sectional relationship between personality traits and regional tau deposition using positron emission tomography (PET) in cognitively normal older adults. A cohort of CN (Clinical Dementia Rating (CDR) 0, n=128) older adults completed the NEO Five-Factor Inventory to assess traits of Neuroticism, Extroversion, Openness, Agreeableness, and Conscientiousness and underwent tau-PET and β-amyloid (Aβ)-PET imaging. We utilized linear regression models, adjusting for age, sex, geriatric depression score, and Aβ to evaluate the association between each of the personality traits and regional tau-PET accumulation. Elevated Neuroticism scores were associated with higher tau-PET accumulation in the amygdala (p=.002), entorhinal cortex (p=.012), and inferior temporal cortex (p=.016), as well as with a composite tau-PET measure (p=.002). In contrast, Extroversion, Openness, Agreeableness, and Conscientiousness were not associated with tau deposition in any of these regions (p’s >0.160). Our results indicate that increased Neuroticism is associated with higher tau pathophysiology in regions known to be vulnerable to AD pathophysiology in CN participants. High Neuroticism scores may therefore serve as a potential risk factor for tau accumulation. Alternatively, personality can change with the onset of AD, thus increased tau levels may affect Neuroticism scores. While future longitudinal studies are needed to determine directionality, our findings suggest early associations between Neuroticism and tau accumulation in CN adults.